India–Sri Lanka Bilateral Relations: Strategic Partnership and Diplomatic Challenges in the 21st Century: भारत–श्रीलंका द्विपक्षीय संबंध: 21वीं सदी में रणनीतिक साझेदारी और कूटनीतिक चुनौतियाँ - Nair, Anila; Aswal, Neha (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
India and Sri Lanka share a long-standing and deep relationship, rooted in common culture, religion, language, and geographical proximity. In the 21st century, these ties have taken a new shape, with growing partnerships in political cooperation, trade, education, health, energy, and maritime security. Today, India is one of Sri Lanka’s major trading partners and is actively involved in several development projects there. Sri Lanka also plays a vital role in India’s security policy in the Indian Ocean. However, the relationship faces several challenges. Issues such as the plight of Tamils in Sri Lanka, disputes over fishing rights, political and economic instability within Sri Lanka, and the rising influence of China continue to test India–Sri Lanka ties. Yet, both countries are making efforts to resolve these problems through dialogue and cooperation. Overall, India–Sri Lanka relations in the 21st century are marked by both opportunities and challenges. With mutual trust and understanding, the partnership has the potential to become a strong foundation for peace and development in the region. Abstract in Hindi Language: भारत और श्रीलंका के रिश्ते बहुत पुराने और गहरे हैं। दोनों देशों को जोड़ने वाली बातें हैं – साझा संस्कृति, धर्म, भाषा और भौगोलिक निकटता। 21वीं सदी में इन रिश्तों ने नया रूप लिया है, जहाँ राजनीतिक सहयोग, व्यापार, शिक्षा, स्वास्थ्य, ऊर्जा और समुद्री सुरक्षा जैसे क्षेत्रों में साझेदारी लगातार बढ़ रही है। भारत आज श्रीलंका का बड़ा व्यापारिक साझेदार है और वहाँ कई विकास परियोजनाओं में सहयोग कर रहा है। हिंद महासागर में भारत की सुरक्षा नीति में भी श्रीलंका की अहम भूमिका है। फिर भी, इन रिश्तों में कई कठिनाइयाँ भी हैं। श्रीलंका में तमिल लोगों का मुद्दा, मछुआरों का विवाद, वहाँ की राजनीतिक और आर्थिक अस्थिरता और चीन का बढ़ता प्रभाव भारत–श्रीलंका संबंधों को चुनौती देते हैं। लेकिन दोनों देश बातचीत और सहयोग से इन समस्याओं को हल करने की कोशिश कर रहे हैं। कुल मिलाकर, 21वीं सदी में भारत और श्रीलंका के रिश्ते अवसरों और चुनौतियों से भरे हुए हैं। अगर दोनों देश आपसी विश्वास और समझ के साथ आगे बढ़ें तो यह साझेदारी क्षेत्र में शांति और विकास का मजबूत आधार बन सकती है। Keywords: ऐतिहासिक निकटता, रणनीतिक महत्व, आर्थिक साझेदारी, बुनियादी ढाँचा सहयोग